Fertilization in Eucalyptus dunnii Maiden in Pampa biome - Brazil - Dick, Grasiele; Schumacher, Mauro Valdir; Araújo, Elias Frank de (Revista Ecologia e Nutrição Florestal - ENFLO, 2021)
In silviculture, mineral fertilization is necessary to supply the nutritional demand, however, the recommendation of the quantities to be applied should aim at maintaining the productive capacity of the soil. The purpose of this study is to test whether increasing the recommended fertilizer dose improves soil fertility and increases the productivity of Eucalyptus dunnii in sites in the central region of the Pampa biome, Brazil. The doses of 150 g (T0), 225 g (T1) and 450 g (T2) of N-P2O5-K2O were applied 24:00:24 per plant, after 14 months of planting. In all tested doses, the species productivity is considered satisfactory for the site. There was an improvement in soil fertility, especially in potassium contents, in addition to a higher individual volume of Eucalyptus dunnii trees after the application of the dose of 450 g plant-1 of N-P2O5-K2O, 24:00:24 in coverage (T2).